Increase in Oxytocin From Skin-to-Skin Contact Enhances Development of Parent–Infant Relationship. Issue 1 (January 2018) - Vittner, Dorothy; McGrath, Jacqueline; Robinson, JoAnn; Lawhon, Gretchen; Cusson, Regina; Eisenfeld, Leonard; Walsh, Stephen; Young, Erin; Cong, Xiaomei
Objective: To examine changes that occur in infant and parent salivary oxytocin (OT) and salivary cortisol (SC) levels during skin-to-skin contact (SSC) and whether SSC alleviates parental stress and anxiety while also supporting mother–father–infant relationships. Methods: This randomized crossover study was conducted in the neonatal intensive care unit (NICU) with a sample of 28 stable preterm infants and their parents. Saliva samples were collected from infants, mothers, and fathers on Days 1 and 2 (1/parent) for OT and cortisol measurement pre-SSC, during a 60-min SSC session, and a 45-min post-SSC. Parental anxiety was measured at the same time points. Parent–infant interaction was examined prior to discharge on Day 3 via video for synchrony and responsiveness using Dyadic Mutuality Coding. Results: Salivary OT levels increased significantly during SSC for mothers ( p < .001), fathers ( p < .002), and infants ( p < .002). Infant SC levels decreased significantly ( p < .001) during SSC as compared to before and after SSC. Parent anxiety scores were significantly related to parent OT and SC levels. Parents with higher OT levels exhibited more synchrony and responsiveness ( p < .001) in their infant interactions. Conclusion: This study addresses a gap in understanding the mechanisms linking parent–infant contact to biobehavioral responses. SSC activated OT release and decreased infant SC levels. Facilitation of SSC may be an effective intervention to reduce parent and infant stress in the NICU. Findings advance the exploration of OT as a potential moderator for improving responsiveness and synchrony in parent–infant interactions.